EqualBITE : gender equality in higher education - Robertson, Judy; Williams, Alison; Jones, Derek; Isbel, Lara; Loads, Daphne; Maxwell, Elspeth (Sense Publishers, 2018)
"The ivory tower, like other stately homes in the UK, might present a grand façade to the world but closer inspection reveals a dark, spidery basement full of inequalities." Gender imbalances still exist across all areas of higher education. From salaries and promotion, to representation in the curriculum, formal approaches and good intentions rarely address the full complexity. EqualBITE digs into the messy reality of higher education gender issues, presenting people's stories, experiences and frustrations and - more importantly - what can be done. University of Edinburgh students and staff share real-life experiences of gender challenges and opportunities, and their constructive responses. The book condenses current academic research into practical actions that do make a difference. EqualBITE is a pragmatic and positive response to gender issues in academia - a catalyst for creating a culture which is better for everyone. "We were so pleased to see this new guide to one aspect of diversity--gender equality--and to see how good it is: the book is comprehensive; it is raw, honest and personal; and it is very well written. It is a book both for reading cover-to-cover and for dipping into, and it will be enormously influential." - Jim Smith Director of Science, Wellcome Trust andamp; Gemma Tracey Diversity andamp; Inclusion Programme Manager - Science andamp; Research, Wellcome Trust "The balance between data and lived experience equip the reader with the vital understanding of the depth of institutionalised inequality...This is recommended reading for anyone working in higher education who truly wants to create a fairer culture of women." - Talat Yaqoob Director, Equate Scotland "I really enjoyed reading the recipes - they combine humour with practical advice on how to tackle important gender issues." - Fiona Watt Vice-Dean Research and Impact, Faculty of Life Science and Medicine, King's College London.